Nanoscale Changes on RBC Membrane Induced by Storage and Ionizing Radiation: A Mini-Review - López-Canizales, Andrea M.; Angulo-Molina, Aracely; Garibay-Escobar, Adriana; Silva-Campa, Erika; Mendez-Rojas, Miguel A.; Santacruz-Gómez, Karla; Acosta-Elías, Mónica; Castañeda-Medina, Beatriz; Soto-Puebla, Diego; Álvarez-Bajo, Osiris; Burgara-Estrella, Alexel; Pedroza-Montero, Martín (Frontiers in Physiology, 2021)
The storage lesions and the irradiation of blood cellular components for medical procedures in blood banks are events that may induce nano changes in the membrane of red blood cells (RBC). Alterations such as the formation of pores and vesicles reduce flexibility and compromise the overall erythrocyte integrity. This review discusses the alterations on erythrocytic lipid membrane bilayer through their characterisation by Confocal Scanning Microscopy, Raman, SEM, and AFM techniques. The interrelated experimental results may address and shed light on the correlation of biomechanical and biochemical transformations induced in the membrane and cytoskeleton of stored and gamma-irradiated RBC. To highlight the main advantages of combining these experimental techniques simultaneous or sequentially, we discuss how those outcomes observed at micro and nanoscale cell levels are useful as biomarkers of cell ageing and storage damage.